12x-7-4x=17+2x+12

Simple and best practice solution for 12x-7-4x=17+2x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-7-4x=17+2x+12 equation:



12x-7-4x=17+2x+12
We move all terms to the left:
12x-7-4x-(17+2x+12)=0
We add all the numbers together, and all the variables
12x-4x-(2x+29)-7=0
We add all the numbers together, and all the variables
8x-(2x+29)-7=0
We get rid of parentheses
8x-2x-29-7=0
We add all the numbers together, and all the variables
6x-36=0
We move all terms containing x to the left, all other terms to the right
6x=36
x=36/6
x=6

See similar equations:

| 4/5n=60 | | 7y+5=3y+17y= | | 2=w-14/2 | | (3x+7)=(3+4x) | | 17=-v+12 | | 12=3.1y–59.3 | | 2w=-6/7 | | -4(u+81)=-4 | | x-40=8(2x+3)-19 | | x/9​=500,000 | | -6(x+24)=42 | | -1/2(x-4)=-8 | | 8+c=-23-25c | | (3x+7)+(3+4x)=180 | | 1/2k=3/k-1/2 | | 5x+20=–5 | | 1/2k=3/k | | 32m+9=86 | | (x^2-3x-28)/(x-1)=x | | 9g-5=3G+37 | | 0.2+2p=75 | | 4x+5x-20+7x-40+6x-40=360 | | −2(x+7)+19=10−3x | | 2.4x+15=2.1x | | x/104=2 | | 1/2(4x-6)=1/2(8x-10) | | 3(2x-2)+10=6(4x+2)+24 | | 0.59x+20=1.09 | | 30-(-6u)=-36 | | 4(2x+1)=4x+6 | | 35^2=b^2+20^2 | | -5x+4+3x=-1-4x-5 |

Equations solver categories